Pengalaman Perilaku Remaja tentang Kesehatan Reproduksi pada Masa Covid-19 di SMK Raflesia Depok 2023 - Johara, Johara; Ita, Ita; Wicaksono, Hendik (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2023)
Teenagers' lack of knowledge about reproductive health can cause various problems with their reproductive health. Reproductive health is important for all groups, especially teenagers. Reproductive health is the guidance of physical, mental or social disabilities, not just the absence of disease or disability but all matters related to the reproductive system, its functions and processes. Understanding reproductive health for teenagers is very important. Many problems will arise if teenagers do not have good knowledge about reproductive health. The Covid-19 pandemic is a difficult situation for all people in the world. There are many behavioral adaptations that people make to survive. This situation has a quite serious impact on access to health services, the economy and social life of the community. This condition also affects the reproductive health of teenagers. This is a type of descriptive qualitative research. This research was carried out in stages and over a certain period of time. Researchers try to collect data through interviews and observations by going directly to the field to meet informants. The data obtained will be presented in the form of descriptive words to make it easier to understand according to what is obtained in the field. Apart from describing it in words, researchers also present data in the form of research photographs to emphasize and clarify the results of the research. Researchers describe the experience of adolescent behavior regarding reproductive health during the Covid-19 period at SMK Raflesia Depok 2023.